2012
DOI: 10.1038/gene.2012.16
|View full text |Cite
|
Sign up to set email alerts
|

Human B-cell ontogeny in humanized NOD/SCID γcnull mice generates a diverse yet auto/poly- and HIV-1-reactive antibody repertoire

Abstract: Characterization of the human antibody (Ab) repertoire in mouse models of the human immune system is essential to establish their relevance in translational studies. Single human B-cells were sorted from bone marrow and periphery of humanized NOD/SCID γcnull mice at 8–10 months post-engraftment with human cord blood-derived CD34+ stem cells. Human immunoglobulin variable heavy (VH) and kappa (Vκ) genes were amplified, cognate VH-Vκ gene-pairs assembled as single-chain variable fragment-Fc antibodies (scFvFcs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 53 publications
3
20
0
Order By: Relevance
“…A subset of these, innate-like B cells, have been described in humans as CD5+ B cells that produce ―natural‖ antibodies which are predominantly IgM, feature low rates of somatic hypermutation, and tend to be auto/poly-reactive, all characteristics that are consistent with observations in BLT mice [21,24]. The small amounts of IgG, as well as the CD27+ B cells occasionally found in the model [21,22,24] do superficially resemble post-germinal center products. However, IgM+ CD27+ B cells are also found in human cord blood and in the absence of traditional memory [26], and can be produced by a germinal center-independent pathway [27].…”
Section: Human Immune Reconstitution and Functionalitysupporting
confidence: 56%
“…A subset of these, innate-like B cells, have been described in humans as CD5+ B cells that produce ―natural‖ antibodies which are predominantly IgM, feature low rates of somatic hypermutation, and tend to be auto/poly-reactive, all characteristics that are consistent with observations in BLT mice [21,24]. The small amounts of IgG, as well as the CD27+ B cells occasionally found in the model [21,22,24] do superficially resemble post-germinal center products. However, IgM+ CD27+ B cells are also found in human cord blood and in the absence of traditional memory [26], and can be produced by a germinal center-independent pathway [27].…”
Section: Human Immune Reconstitution and Functionalitysupporting
confidence: 56%
“…We took advantage of the humanized NOD- scid IL2r γ null mouse model system described by Notta et al (24), because these mice were reported to generate multilineage human hematopoietic cells, including antibody producing B cells (3033). CD34 + HSPCs from 6 ARID3a H and 6 ARID3a L samples were injected into NSG mice and analyzed for engraftment potential according to the diagram shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other investigators have also reported a diverse TCR and IgH repertoire, similar to that seen in humans, without suggestion of lymphopenia-induced proliferation [17]: a diversified repertoire approaching 100% of human reference samples with no major alterations. Other investigators have characterized the B cell repertoire in NSG mice 8-10 months after engraftment with CB CD34 + stem cells and reported the BCR repertoire to be large but predisposed towards autoreactivity, indicative of defects in selection [4].…”
Section: Discussionmentioning
confidence: 99%
“…There have been questions as to whether a truly functional (as opposed to phenotypic) human immune system develops, whether it represents a diverse and properly restricted adaptive immune system [focused upon recognition of human leucocyte antigen (HLA) molecules], and if all parts of the innate immune system are intact. Data have been published to support and refute each of these claims [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%